Determinants affecting house purchase intention among selected consumers in Johor Bahru / Nurul Rabihah Ismail - Ismail, Nurul Rabihah (Faculty of Business and Management, 2018)
Picking out a dream house to purchase can be simultaneously exciting and horrifying. Especially when it is not just a negotiation for merchandize, it is a place where we tend to live and call home. However, buying a house in this 21st century comes with a hurdle as the world population tends to grow year by year and may never possibly decline. In Johor Bahru, Malaysia, the demand and supply of housing keeps increasing, yet there is still a large figure of unsold units in the market. This study reviewed several theories related to financial, location and house attributes as possible avenues towards a framework of determining what factor affects the house purchase intention of selected consumers in Johor Bahru. A convenience sampling technique was used in this research. A sample of 384 respondents living in Johor Bahru was taken from a targeted population of 1, 494, 800 had been examined. Data collected are then analyzed and findings were generated using Frequency Distribution Analysis, Descriptive Analysis, Pearson Correlation Analysis, Multiply Regression Analysis, and Reliability Analysis with the aid of Statistical Package for Social Sciences (SPSS) version 23. Meanwhile, figures, tables and charts were used for data presentation. The findings of this study have shown that all three out of three hypotheses were accepted. The variables that were included in the accepted hypotheses are financial, location and house attributes. Relatively, learning the purchase intention behavior in the market is a reliable process to stimulate information in order to have a better understanding on the way the consumers think and perceive.